PULSE WAVE VELOCITY AND CENTRAL AORTIC PRESSURE IN OBESE CHILDREN ACCORDING TO THE NON-INVASIVE ARTERIOGRAPHY RESULTS - O. V. Kozhevnikova; L. S. Namazova-Baranova; O. S. Logachyova; T. V. Margieva; I. V. Shirokova; A. N. Rakhimova; A. S. Balabanov (Педиатрическая фармакология)
The article presents information value of non-invasive arteriography, which reveals early signs of cardiovascular pathology formation in children, using a large number of trials in children. The authors examined predictors of cardiovascular catastrophes’ development, confirmed in adults: aortic wall’s stiffness, central aortic pressure and pulse pressure – that have not been sufficiently studied in children yet. The article shows that the high-technology method of non-invasive arteriography allows revealing changes of these parameters in children on the preclinical stage. It also shows their correlation with body mass index, fatty hepatosis, direct correlation of weight gain with connection of pulse wave velocity and central blood pressure and importance of follow-up evaluation of these parameters. Heterogeneity of the group of obese children in terms of these parameters is a premise for development of individual approach to control and prevention of cardiovascular complications’ development risk in childhood.